Zanthoxylum armatum DC extracts from fruit, bark and leaf induce hypolipidemic and hypoglycemic effects in mice- in vivo and in vitro study - Fiaz Alam; Qazi Najam us Saqib; Mohammad Ashraf (BMC, 2018)
Abstract Background Zanthoxylum armatum DC is an important medicinal plant of south East Asia, and has been used to treat various ailments in traditional medicine including diabetes. This study investigated the in vitro and in vivo antidiabetic and biochemical effects of extracts of Z. armatum in mice. Method The extracts of fruit, bark and leaf from Z. armatum were tested for α-glucosidase inhibition activity. Albino mice of either sex weighing (26-30 g) assigned into groups. Diabetes was induced by IP injection of alloxan monohydrate (150 mg/kg). The extracts (500 mg/kg) and standard (Glibenclamide 10 mg/kg) were administered to mice for 15 days. Serum biochemical parameters were monitored for the period of study. Results The leaves and bark extracts showed maximum α-glucosidase inhibition (96.61 ± 2.13 and 93.58 ± 2.31% respectively). The extracts treated and the standard treated groups showed significant decrease in the fasting blood glucose levels compared to diabetic control. The effect was more pronounced in mice treated with leaves extract. In the in vivo studies body weights of diabetic mice treated with Z. armatum extracts and the standard did not reduced to extent as observed in diabetic control and this difference was significant (p < 0.05). There was a significance (p < 0.001) improvement in blood hemoglobin, urea, creatinine, cholesterol, and triglycerides of the extracts treated diabetic mice. The extracts showed hypolipidemic effect by reducing the LDL level. The extracts produced no prominent changes in proteins levels. Conclusion It can be concluded that Z. armatum extracts showed excellent antidiabetic potential in vivo and in vitro and could be considered for further appraisal in clinical assessment and drug development.